Analisis Rasio Keuangan Pada Financial Distress Perusahaan Retail Yang Terdaftar Di Bei (2016 – 2019) - Lutfianan Nur Azizah; Arisyahidin Arisyahidin (Otonomi, 2021)
This study aims to determine the effect of profitability, liquidity, leverage, and activity in predicting financial distress conditions in retail companies on the Indonesia Stock Exchange (IDX) for the period 2016-2019. The sampling technique used was purposive sampling with a number of selected samples of 18 companies. The number of samples used was as many as 7 companies in the category of experiencing financial distress and 11 companies in the category did not experience financial distress. The results of the study using logistic regression show that profitability measured by the Return on Investment (ROI) has a negative effect on financial distress. Liquidity as measured by Current Ratio (CR) has a negative effect on financial distress. Leverage measured by Debt to Equity Ratio (DER) has a negative effect on financial distress. Activity measured by Fixed Assetss Turnover (FAT) not has a effect on financial distress.